The effect of service quality in moderating the influence of brand image and marketing mix on consumer purchase decisions motorku multipurpose products - Hastomo Nugroho; Rudy C. Tarumingkeng; Eka Desy Purnama (Institute of Computer Science (IOCS), 2023)
The development of the financing industry has increasingly created competition, especially during and after the Covid-19 pandemic. Sales data for the last four years of the multipurpose product MotorKu WOM Finance Purwokerto (2019-2022) recorded fluctuating numbers. In 2020 and 2021 there will be a decrease in sales compared to 2019, this indicates a decrease in purchasing decisions by consumers, one of which is due to the conditions of the Covid-19 pandemic crisis which has caused decreased income and people's purchasing power. However, sales profit from MotorKu product is the biggest contributor for branch profit. So, that is needed efforts to increase sales to boost profit growth in line with the post-Covid-19 economic improvement. This study aims to determine the effect of service quality in moderating the effect of brand image and the marketing mix on consumer purchasing decisions for PT MotorKu multipurpose products. WOM Finance Purwokerto Branch. The sample in this study was 140 respondents from a total population of 1338. The data were obtained through random distribution of questionnaires. Data analysis technique uses SmartPLS version 3.3.3 software. From the results of the analysis it was found that brand image and marketing mix each had a significant positive effect on consumer purchasing decisions, service quality had a negative significant effect in moderating the effect of brand image on consumer purchasing decisions, and service quality had a significant positive effect in moderating the effect